(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Today human activities are constantly adding industrial, domestic and agricultural wastes to river water and ground water reservoirs at an alarming rate. Ground water contamination is generally irreversible ones it is contaminated, it is difficult to restore the original water quality of the aquifer. Excessive mineralization of ground water degrades water quality producing an objectionable taste, odor and excessive hardness. Industrial Effluents discharged into water bodies contain toxic chemicals. Effluents from urban areas contain large concentration of oils, greases, nutrients, heavy metals and detergents. The detergents being soluble can pass through the soil and pollute ground water. Raw sewage dumped in shallow soak pits and seepage from polluted lake, pond or stream also polluted water. Rainfall could pick up substantial contaminants from dust and air and join the aquifer below. The infiltration of liquids containing toxic pollutants may cause pollution